SCHOOL CULTURE AND PROFESSIONAL DEVELOPMENT OF SCHOOL TEACHERS FROM URBAN AND RURAL AREAS IN CHINA - Zhang Ling; Jiang Na; Siaw Yan-Li; Joko Sriyanto (LPMPP Universitas Negeri Yogyakarta, 2020)
Rural teacher recruitment and retention has become a common concern globally including in China. In order to understand the underlying reasons that cause rural teachers’ attrition, this study aims to explore the school culture and professional development of the teachers from urban and rural areas of China provinces, by examining three study objectives: teaching location and socio-demographic factor; challenges faced by rural teachers; and strategies to develop teaching professionalism in rural schools. A mixed-method approach involving survey forms and interview sessions was used for data collection. Data were analyzed using SPSS and ATLAS.ti which included inferential and thematic analysis. A number of 1547 teachers under Compulsory Education in Jiangxi, China were involved as participants. Results indicated that teaching location is significantly related to the socio-demographic condition. Additionally, five challenges reported by rural school teachers include parental involvement, working environment, salary, personal growth, and family environment. Meanwhile, three main strategies used for professional development are educational beliefs, collaboration relationships, and teacher self-training. The outcome of this study would contribute towards effective and feasible measures to stabilize rural teachers, promote educational and social equity, and promote the integration of urban and rural teachers. Findings conclude the importance to explore further and propose the corresponding measures to improve the working and living status of rural teachers.